The socio-occupational vulnerability of Brazilian domestic workers during the coronavirus pandemic: The aggravation of social injustices - Stolz, Sheila; Flores Gusmão, Carolina (Revista Chilena de Derecho del Trabajo y de la Seguridad Social, 2021)
The outbreak of the COVID-19 pandemic in Brazil demonstrated the mar ginalized situation in which domestic workers are. The biggest country in the world in domestic worker population, with around 7 million domestic workers, has not estab lished a national health plan to deal with the virus. Though some specific measures were taken, especially involving the economy, domestic workers remained as one of the most affected sectors in Brazil, both economically and in terms of health. This article aims to present, first, an overall view of domestic workers’ condition, taking into account ordinances and the social structure involving domestic work in Brazil. Then, because of the outbreak of the COVID-19 pandemic in Brazil, it is presented how domestic workers were particularly affected. Considering that domestic work is a job essentially done by women and mostly black women from lower social classes, this study is outlined by the theories of intersectionality and social justice.